A Comparative Study on the Efficacy of NLRP3 Inflammasome Signaling Inhibitors in a Pre-clinical Model of Bowel Inflammation - Pellegrini, Carolina; Fornai, Matteo; Colucci, Rocchina; Benvenuti, Laura; D’Antongiovanni, Vanessa; Natale, Gianfranco; Fulceri, Federica; Giorgis, Marta; Marini, Elisabetta; Gastaldi, Simone; Bertinaria, Massimo; Blandizzi, Corrado; et al. (Frontiers in Pharmacology, 2018)
Nucleotide-binding oligomerization domain leucine rich repeat and pyrin domain-containing protein 3 (NLRP3) inflammasome is pivotal in maintaining intestinal homeostasis and sustaining enteric immune responses in the setting of inflammatory bowel diseases. Drugs acting as NLRP3 blockers could represent innovative strategies for treatment of bowel inflammation. This study was performed in rats with dinitrobenzenesulfonic acid (DNBS)-induced colitis, to investigate how the direct blockade of NLRP3 inflammasome with an irreversible inhibitor (INF39) compares with Ac-YVAD-cmk (YVAD, caspase-1 inhibitor) and anakinra (IL-1β receptor antagonist), acting downstream on NLRP3 signaling. Animals with DNBS-colitis received YVAD (3 mg/kg) or anakinra (100 mg/Kg) intraperitoneally, and INF39 (25 mg/kg) or dexamethasone (DEX, 1 mg/kg) orally for 6 days, starting on the same day of colitis induction. Under colitis, there was a body weight decrease, which was attenuated by YVAD, anakinra or INF39, but not DEX. All test drugs counteracted the increase in spleen weight. The colonic shortening and morphological colonic alterations associated with colitis were counteracted by INF39, anakinra and DEX, while YVAD was without effects. Tissue increments of myeloperoxidase, tumor necrosis factor and interleukin-1β were more effectively counteracted by INF39 and DEX, than YVAD and anakinra. These findings indicate that: (1) direct inhibition of NLRP3 inflammasome with INF39 is more effective than caspase-1 inhibition or IL-1β receptor blockade in reducing systemic and bowel inflammatory alterations; (2) direct NLRP3 inhibition can be a suitable strategy for treatment of bowel inflammation.